Complete mitochondrial genome sequence of Romanogobio tenuicorpus (Amur whitefin gudgeon). (2nd November 2015) - Dong, Fang; Tong, Guang-Xiang; Kuang, You-Yi; Sun, Xiao-Wen
Abstract: Amur whitefin gudgeon ( Romanogobio tenuicorpus ) belongs to the family Cyprinidae, it is freshwater aquaculture species in China. In the report, we determined the complete mitochondrial genome sequence of Romanogobio tenuicorpus, which is 16, 600 bp long circular molecule with 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and a control region, the conserved sequence blocks, CSB1, CSB2 and CSB3 were also detected.